Irrigated Agriculture and Poverty Reduction in Kassena Nankana District in the Upper-East Region, Ghana (Journal of Science and Technology, 2016)
In northern Ghana, where the climatic conditions do not allow for an all-year-around rain-fed agriculture, irrigation is a necessary complement to enhance livelihoods security and poverty reduction. The knowledge gap regarding the contribution of existing irrigation facilities to poverty reduction occasioned the case study of the Tono irrigation scheme located in the Kassena Nankana District in the Upper East Region of Ghana. A treatment and control experimental approach was adopted in the investigation. The treatment group comprised a sample of 93 out of the 1,328 Tono irrigation tomato farmers and the control group sampled 86 out of 614 irrigation tomato farmers operating outside the Tono irrigation scheme. The Tono irrigated scheme has, to a considerable extent, created a platform for employment and high agricultural output. However, the high agricultural output has not been translated into increased income and improved livelihoods for the farmers and as such limits the impact of the efforts exerted towards poverty reduction amongst the farmers in the area. The challenges that led to this outcome include high cost of hiring farm machinery, inadequate access to credit, poor water supply for irrigation, ineffective technical assistance, lack of entrepreneurial skills, inability to store perishable products and inadequate ready market to translate the outputs into improved incomes for the farmers. Actors in the irrigated agriculture industry should pay equal attention to both the production and marketing aspects of their enterprises. The actors should ensure that the necessary inputs are available and affordable to farmers